Evaluating the effectiveness of an islamic-integrated mindfulness-based academic resilience program on academic resilience and emotional regulation - Handayani Sura'; Ismail ismail; Muhammad Junaedi Mahyuddin (Jurnal Konseling dan Pendidikan, 2025)
University students frequently experience academic stress that may undermine emotional regulation and adaptive academic functioning. Academic resilience has been identified as a protective factor that enables students to cope effectively with academic challenges. This study examined the association between participation in an Islamic-integrated Mindfulness-Based Academic Resilience (MBAR) program and changes in academic resilience and emotional regulation among undergraduate students. A quasi-experimental pretest-posttest control group design was employed involving 60 fourth-semester students from the Guidance and Counseling Study Program at Universitas Muhammadiyah Enrekang. The experimental group participated in twelve structured sessions combining mindfulness practices with Islamic contemplative elements, while the control group received no intervention. Data were collected using validated self-report scales, observation sheets, and semi-structured interviews. Paired and independent samples t-tests were conducted to examine within- and between-group differences, and effect sizes were calculated. Results indicated statistically significant improvements in academic resilience and emotional regulation in the intervention group compared to the control group, with large effect sizes observed at posttest. Qualitative findings suggested increased emotional awareness, cognitive reframing, and perceived academic coping capacity among participants. However, given the quasi-experimental design, single-institution sample, and reliance on self-report measures, causal interpretations and generalizability should be approached cautiously. The findings provide contextually grounded empirical evidence regarding the short-term association between structured mindfulness practice and adaptive academic functioning within a faith-based Indonesian higher education setting